Management of Technical Employees in the Involvement of Coordination and Collaboration - Elea Imarisha (Journal of Management and Administration Provision, 2022)
This article explores the challenges faced by organizations in managing technical employees in a coordinated and collaborative environment. The authors argue that effective coordination and collaboration between technical employees and management is crucial for achieving organizational goals and enhancing job satisfaction among employees. The article highlights the importance of clear communication and a supportive work environment, and emphasizes the need for managers to be knowledgeable about technical aspects and flexible in their approach to problem-solving. The authors provide practical suggestions for overcoming these challenges and offer insights into the importance of successful coordination and collaboration in the management of technical employees. the article examines the role of technology in facilitating coordination and collaboration between technical employees and management. It also discusses the need for continuous training and professional development for technical employees to stay up-to-date with the latest advancements in their field. The authors suggest that a combination of effective communication, collaboration, and technology can lead to improved productivity, better quality of work, and increased job satisfaction among technical employees. The findings of this article offer valuable insights into the management of technical employees in the modern work environment and have implications for organizations looking to improve their management practices and achieve success in a rapidly changing technical landscape.